2017
DOI: 10.1111/gcb.13918
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced‐efficiency fertilizers are not a panacea for resolving the nitrogen problem

Abstract: Improving nitrogen (N) management for greater agricultural output while minimizing unintended environmental consequences is critical in the endeavor of feeding the growing population sustainably amid climate change. Enhanced-efficiency fertilizers (EEFs) have been developed to better synchronize fertilizer N release with crop uptake, offering the potential for enhanced N use efficiency (NUE) and reduced losses. Can EEFs play a significant role in helping address the N management challenge? Here we present a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
152
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(168 citation statements)
references
References 26 publications
9
152
5
2
Order By: Relevance
“…In contrast, other authors have shown a reduction of NH 3 emissions by double inhibition with urea compared with urea alone [see Li et al. () and Kanter and Searchinger () for reviews].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, other authors have shown a reduction of NH 3 emissions by double inhibition with urea compared with urea alone [see Li et al. () and Kanter and Searchinger () for reviews].…”
Section: Discussionmentioning
confidence: 89%
“…Globally, urea is the N‐fertilizer most widely applied in modern agriculture, and its use has increased 100‐fold in the last 50 years mainly due to its low cost ( Thompson and Meisinger , ; Glibert et al., ; Heffer and Prud'homme , ). Among the management strategies to improve the N use efficiency of fertilizers and to mitigate gas emissions, urease and nitrification inhibitors could be used to reduce NH 3 and N 2 O emissions ( Li et al., ). Urease is the enzyme responsible for the conversion of urea into carbon dioxide (CO 2 ) and NH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Across many studies, nitrification inhibitors alone or combined with urease inhibitors have resulted in a consistent decrease in N 2 O emissions on average (Table 2), with effect sizes ranging from 8 to 100% (Snyder et al, 2009; Qiao et al, 2015; Thapa et al, 2016; Lam et al, 2017; Li et al, 2018). In one meta‐analysis, nitrification inhibitors reduced N 2 O emissions across different land uses, climatic conditions, and for a range of soil texture and pH (Li et al, 2018).…”
Section: Do Stabilized Nitrogen Sources Consistently Reduce N2o Emissmentioning
confidence: 98%
“…Pan et al (2016) reported that urease inhibitors decreased NH 3 emissions by 54%, whereas Saggar et al (2013) reported a 45% reduction. Urease inhibitors mitigated NH 3 volatilization across a range of soil types and pH, land use, and annual precipitation gradient (Li et al, 2018). However, high soil carbon content and temperatures may potentially reduce the efficacy of urease inhibitors (Saggar et al, 2013).…”
Section: Do Stabilized Nitrogen Sources Decrease Nh3 Volatilization?mentioning
confidence: 99%
See 1 more Smart Citation